2014
DOI: 10.1007/s13277-014-2739-6
|View full text |Cite
|
Sign up to set email alerts
|

Higher circulating levels of chemokine CCL22 in patients with breast cancer: evaluation of the influences of tumor stage and chemokine gene polymorphism

Abstract: The receptor for CCL22 is named CCR4 that preferentially is expressed on the regulatory T cells (Treg), and accordingly, CCL22 acts as a chemoattractant for the intratumoral Treg migration. The aim of this study was to evaluate the serum CCL22 levels and a single nucleotide polymorphism (SNP) in chemokine gene, [2030 G/C (rs223818)], in patients with breast cancer. Blood samples were collected from 100 women with breast cancer before receiving chemotherapy, radiotherapy, or immunotherapy and 100 age-matched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 54 publications
5
53
1
Order By: Relevance
“…In numerous cancer types including melanoma [7], breast carcinoma [31-33], and prostate carcinoma [34], amongst others [35, 36], circulating inflammatory cytokine [34], chemokine [32, 37], enzyme [31], exosome [7], and/or microvesicle [35] levels and qualities are altered relative to healthy controls and with respect to disease stage in both patients and pre-clinical tumor models. These changes have been attributed to both higher production of such factors within the tumor [14, 31, 37] and extratumoral host tissue response to tumor growth [38].…”
Section: Discussionmentioning
confidence: 99%
“…In numerous cancer types including melanoma [7], breast carcinoma [31-33], and prostate carcinoma [34], amongst others [35, 36], circulating inflammatory cytokine [34], chemokine [32, 37], enzyme [31], exosome [7], and/or microvesicle [35] levels and qualities are altered relative to healthy controls and with respect to disease stage in both patients and pre-clinical tumor models. These changes have been attributed to both higher production of such factors within the tumor [14, 31, 37] and extratumoral host tissue response to tumor growth [38].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies investigating the expression of IL‐33 levels in cancer have yielded conflicting results. Some authors reported a highly expressed concentration of IL‐33 in serum and tumour tissues of ovarian cancer, breast cancer, gastric cancer, non‐small cell lung cancer, colorectal cancer and squamous cell carcinoma of tongue . The higher IL‐33 expression predicted a worse prognosis and progression‐free survival after chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that MDC was up-regulated in some tumor entities, suggesting its oncogenic potentials [27, 28]. The down-regulation of MDC in turn suggested its tumor suppressive potentials [29].…”
Section: Discussionmentioning
confidence: 99%